2010
DOI: 10.1111/j.1399-3054.2010.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Shading the whole vines during young fruit development decreases ascorbate accumulation in kiwi

Abstract: We investigated how different lighting conditions affected the levels of ascorbate (AsA), sugar contents, the mRNA expression of genes involved in AsA biosynthesis and recycling and enzyme activity in kiwi fruits. Shaded leaves had dramatically less AsA as well as altered transcript levels and enzyme activities. In contrast, fruits that had been covered directly at various developmental stages showed no changes in those parameters. Fruits had significantly less AsA content before 40 days after anthesis (DAA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In this study, we only detected the simultaneous sugar content and gene expression of AA L-galactose pathway-related enzymes since the focus of the study was to investigate the response of fruit ASC to BG. A strong correlation between sugar and AA content was found in other reports (Richardson et al 2004;Yabuta et al 2007;Gautier et al 2009;Li et al 2009;Li et al 2010). In the present study, we found that ASC and TSS contents or soluble sugar components changed in parallel in the pulp of fruits exposed to BG (Figs.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we only detected the simultaneous sugar content and gene expression of AA L-galactose pathway-related enzymes since the focus of the study was to investigate the response of fruit ASC to BG. A strong correlation between sugar and AA content was found in other reports (Richardson et al 2004;Yabuta et al 2007;Gautier et al 2009;Li et al 2009;Li et al 2010). In the present study, we found that ASC and TSS contents or soluble sugar components changed in parallel in the pulp of fruits exposed to BG (Figs.…”
Section: Discussionsupporting
confidence: 88%
“…It is known that light exposure increased ASC production in plants (Smirnoff, 2000; Tabata et al, 2002). Recently, it has been reported that a light-dependent increase in ASC occurs in both fruits and leaves being stronger in the latter (Li et al, 2010b; Massot et al, 2012). This is consistent with the pivotal role of ASC in the chloroplastic photo-protecting mechanisms: it is cofactor of violaxanthine de-epoxidase, an enzymes involved in the xanthophyll cycle, and the major player of the water–water cycle, two pathways preserving photosynthetic components by the photo-oxidation due to high irradiance-dependent ROS release (Eskling et al, 1997; Asada, 2000).…”
Section: Strategy Of Biofortificationmentioning
confidence: 99%
“…The biosynthesis of ascorbic acid in plants has been the aim of many investigations, basically in species destined for human consume. Thus, although the main pathways involved in such event have been well established so far [103] , [23] , [52] , [64] , [90] , [97] , [100] , transcription and expression studies were achieved during last years in order to understand the complex regulation of those routes [104] , [107] , [108] , [29] , [49] , [62] , [65] .…”
Section: Introductionmentioning
confidence: 99%